2001
DOI: 10.2223/jped.356
|View full text |Cite
|
Sign up to set email alerts
|

Devic disease: a case report

Abstract: Artigo submetido em 27.09.00, aceito em 30.05.01. ResumoObjetivo: chamar a atenção para o diagnóstico da doença de Devic e realizar revisão da literatura.Descrição: paciente de 6 anos, do sexo masculino, apresentou subitamente paresia nos membros inferiores, que desapareceu no decorrer da internação. No entanto, à medida que a paresia desaparecia, ocorria perda da visão. Os sintomas só foram revertidos após o uso de prednisona.Comentários: a abordagem diagnóstica e terapêutica foi semelhante à usada em outros … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Rilling et al (1999) showed use of Methylprednisolone improved symptoms for a while and cyclophosphamide was used to prevent recurrence. 3 Mandler et al (1998) found no recurrence for 18 months in patients treated with prednisolone and azathioprine for 2 months. 3,8 Prognosis is guarded for NMO or NMO spectrum disorders.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Rilling et al (1999) showed use of Methylprednisolone improved symptoms for a while and cyclophosphamide was used to prevent recurrence. 3 Mandler et al (1998) found no recurrence for 18 months in patients treated with prednisolone and azathioprine for 2 months. 3,8 Prognosis is guarded for NMO or NMO spectrum disorders.…”
Section: Discussionmentioning
confidence: 98%
“…3 Mandler et al (1998) found no recurrence for 18 months in patients treated with prednisolone and azathioprine for 2 months. 3,8 Prognosis is guarded for NMO or NMO spectrum disorders. Studies show 20% patients to be functionally blind in at least 1 eye and 31% developed permanent monoplegia/paraplegia.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation